PENGARUH INTELLECTUAL CAPITAL DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BEI TAHUN 2020-2023 - Fidya Nurafni Ulhaq; Jacobus Widiatmoko; Maria Goerti Kentris Indarti (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research was conducted to examine the influence of intellectual capital and corporate governance on earnings management with company size, leverage, profitability as control variables. The population in this research is sub-textile and garment companies listed on the Indonesia Stock Exchange in 2020-2023. Data is analyzed as secondary taken from financial reports listed on the Indonesian Stock Exchange. Sample selection was carried out using a purposive sampling technique, so that a sample of 80 data was analyzed. The analytical method used in this research is the multiple linear regression method. The research results show that intellectual capital has a negative effect on earnings management, the board of commissioners, independent audit committee and audit quality have a negative effect on earnings management.